Radiofrequency Echographic Multi-Spectrometry in the Diagnosis of Metabolic Bone Disease - Gifuni, Rossella; Montatore, Manuela; Guglielmi, Riccardo; Bazzocchi, Alberto; Messina, Carmelo; Guglielmi, Giuseppe (Seminars in Musculoskeletal Radiology, 2024)
Dual-energy X-ray absorptiometry (DXA) and bone mineral density (BMD) pose several limitations in some patient categories, such as pregnant women and young people. This review article explores whether the innovative radiofrequency echographic multi-spectrometry (REMS) technology is beneficial for assessing the bone condition of various patient groups. Common consequences in patients with acromegalia, prostate cancer undergoing hormone therapy, osteogenesis imperfecta, anorexia nervosa, and in a peritoneal dialysis setting include decreased BMD and an increased risk of fragility fracture.DXA is currently regarded as the gold standard for BMD assessment. However, using the DXA technique has several drawbacks in a young patient who requires repeated BMD tests because it uses ionizing radiation. Because of its precision and consistency, the REMS technique may be a valuable tool to assess changes in bone condition in patients of all ages, particularly in female patients who are fertile or who are pregnant or nursing.
Keywords: bone mineral density; osteoporosis; radiofrequency echographic multi-spectrometry; bone health status